Penguatan Kemandirian Ekonomi Berbasis Ketahanan Pangan Keluarga di Desa Dersalam, Kecamatan Bae, Kabupaten Kudus - Lusianti, Dina; Indaryani, Mamik; Septanti, Annisya; Hendriyanto, Dennyca; Sudarsono, Sudarsono (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Assistance activities to achieve economic self-sufficiency that is based on food resilience. Cultivating plants such as chilies, eggplants, tomatoes and the technique of cultivating plants in buckets is believed to bring benefits. With the presence of food plants, we can provide a healthy food supply that is easily accessible, affordable and nutritious. Not only that, food security can have an impact on economic independence. Research methodology: This service activity includes counseling in the form of lectures which aims to enrich food plant literacy. Followed by cultivation practices using the method of cultivating plants in buckets. To provide motivation, seeds are given as a form of stimulant and trigger for program sustainability. The targets for this activity are residents of Dersalam, Bae District, Kudus Regency, Central Java. Results: Increasing partners' economic self-sufficiency through food resilience and the success of the program can be seen in the level of expenditure of partners who previously had to spend at least an average of IDR 5,000 per day per family to buy vegetables and catfish. Limitations: This activity is limited to certain plants, such as eggplant, chilies, mustard greens, tomatoes and kale. Contribution: a food resilience-based approach has a key role in increasing community economic self-sufficiency. The implementation of activities focuses on counseling and assistance to achieve economic self-sufficiency, with an emphasis on plant literacy, land preparation, plant selection, and the use of organic fertilizer.